KUASO BETINO RIMBO : Potret Perempuan dalam Keluarga Rimba - Ahmad Syarifin (Kafa`ah: Journal of Gender Studies, 2014)
The relation between masculinity and femininity in the jungle family has a vital position. In inheritance case, a divorce, either life or death, causes several rights that belong to women such as child custody, property split (community or separate property. This nature resource inheritance status covers an ownership, utilization, and distribution for example in agricultural or hunted resource. However, social changes affect female (batino) role in a domestic field. She takes care not only for women responsibilities such as child care, household task, cooking and serving the husband, but also takes care of men’s responsibilities  such  as  providing  water  from  the  river,  collecting wood, farming and other activities that men should do.  Keywords: power, women, and jungle familyCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.97